Temperate livestock production and health - Pandey, A. B. (Indian Farming, 2015)
The IVRI Research Station at Mukteswar, is involved in variousresearch activities through its central facilities like Biotechnologylaboratory, Central Instrumentation Unit, Section on Extensioneducation, the agricultural farm and the orchard. The main work is carried out in its Division of Virology and Division of Temperate Animal Husbandary and extension services of education and trainings for technology awareness among farmers is carried out by its Extension Division.